2017
DOI: 10.1088/2053-1583/aa5c64
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the terahertz nonlinearity of graphene by orientation disorder

Abstract: Abstract. The conical band structure is the cornerstone of graphene's ultra-broadband optical conductivity. For practical use of graphene in nonlinear photonics, however, substantial increases of the light-matter interaction strength will be required while preserving the promising features of monolayers, as the interaction of light with a single atomic layer is limited due to the extremely short interaction length and low density of state, particularly for the long-wavelength region. Here, we report that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…To break through these substantial limitations, graphene has attracted attention owing to its gapless and linear energy spectrum and massless Dirac Fermions, giving rise to superior carrier transport properties [27][28][29][30][31]. The latest studies have reported on the potential of relatively simpler multi-layer graphene devices [32,33] to more complex graphene/h-BN heterostructures [34,35] for highly sensitive detection as well as emission of THz radiation [35].…”
Section: Introductionmentioning
confidence: 99%
“…To break through these substantial limitations, graphene has attracted attention owing to its gapless and linear energy spectrum and massless Dirac Fermions, giving rise to superior carrier transport properties [27][28][29][30][31]. The latest studies have reported on the potential of relatively simpler multi-layer graphene devices [32,33] to more complex graphene/h-BN heterostructures [34,35] for highly sensitive detection as well as emission of THz radiation [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that the modulation depth of graphene could be significantly improved by the random stacking of layers with orientational disorder. This fact suggests that further enhancement of the absorption nonlinearity of SnSe could be possible if its layers are stacked with random orientation . The time‐bandwidth product of 0.397 indicates that the output pulses were slightly chirped in our laser system.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, randomly stacked multilayer graphene can be treated as multiply electronically decoupled monolayer graphene. 30,31 The silicon prohibited bandwidth was 1.12 eV, while the silicon cutoff wavelength for its intrinsic leap was 1107 nm. We used a 975 nm CW laser as an excitation source to generate photo-generated carriers.…”
Section: Resultsmentioning
confidence: 99%